A facile approach to fabricate porous UMCM-150 nanostructures and their adsorption behavior for methylene blue from aqueous solution1. Issue 26 (14th July 2015) - Yang, Ji-Min; Liu, Qing; Kang, Yan-Shang; Sun, Wei-Yin
<x xml:space="preserve">Abstract</x> UMCM-150 nanostructures with different sizes and shapes were synthesized and found to exhibit excellent adsorption capability for MB.